MELESTARIKAN BAHASA SASAK MELALUI CERITA-CERITA RAKYAT PADA LINGKUNGAN KELUARGA DAN SEKOLAH UNTUK ANAK USIA DINI YANG DITINJAU DARI PENDEKATAN SOSIOLINGUISTIK - Baiq Yulia Kurnia Wahidah (LPPM Institut Pendidikan Nusantara Global, 2020)
This study aims to describe the linguistic data relating to language preservation planning in children through the family and school environment in a folklore. The method of this research is a descriptive caucasian which describes the effect of using folktales to preserve the Sasak language. In analyzing the data in the form of linguistic data containing moral values that can be taught to children through folklore and can strengthen the pelakatrian Sasak language. The results of this study are the discovery of factors that can influence pelelsatrian Sasak language through folklore. Children can also catapult Sasak languages starting from sitting in kindergarten so that Sasak is not extinct.